Playing Time-Variant Audio Feedback Networks - Monteiro, Adriano Claro (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19443, 2021)
This article presents practical and artistic contributions to the field of computational musical systems based on audio feedback networks which have been used as instruments for music creation in the author's artistic practice. The article begins with an introduction to the research field of feedback and selforganized music systems. Later on two systems are presented: the first is a network of cross-modulated sinusoidal oscillators (by frequency modulation), and the second is a network of transforming processes of pre-recorded sound samples.